Co-small Module - Li, Wang; Jin, Cuncheng (Journal of Informatics and Mathematical Sciences, 2015)
The main goal of the present article is to study basic properties of co-small modules. Let R be a Noetherian ring, For all co-small module B and index I, we get isomorphic Torn(B;A_i)Torn(B;A_i). Finally, we prove that If two modules of the sequence 0 → A→ B→ C→ 0 are co-small modules, so is the third.